Functional Thinking in Mathematics Learning: What and How to Measure it? - Ratnasari, Gamarina Isti; Widjajanti, Djamilah Bondan; Andayani, Sri (Indonesian Journal of Educational Research and Review, 2023)
Functional thinking becomes a principle in the process of learning mathematics at school. Even though the need for a review of functional thinking is increasing, until now there has been no systematic literature review discussing what and how to measure functional thinking in mathematics learning. The aim of this study is to analyze the importance of functional thinking in mathematics learning and how to measure functional thinking. The method used in this systematic review study refers to PRISMA. The total articles collected were 5,415,874. Based on the PRISMA steps which consist of Identification, Screening, Eligibility, and Included, 63 articles met the requirements. The results of a review of 63 articles show that there are several things that must be considered in developing functional thinking in learning mathematics such as using open problems, solving realistic problems, using technology, and giving routine and non-routine practice questions. Furthermore, in measuring functional thinking, it can be seen based on the indicators, namely writing the next element based on the previous pattern (recursive pattern), using the relationship between elements to continue the relationship to elements in general (covariational relationship), and stating the relationship between two elements that vary in the form of function rules (correspondence).